2021
DOI: 10.3390/biomedicines9091246
|View full text |Cite
|
Sign up to set email alerts
|

Oral Capsaicinoid Administration Alters the Plasma Endocannabinoidome and Fecal Microbiota of Reproductive-Aged Women Living with Overweight and Obesity

Abstract: Capsaicinoids, the pungent principles of chili peppers and prototypical activators of the transient receptor potential of the vanilloid type-1 (TRPV1) channel, which is a member of the expanded endocannabinoid system known as the endocannabinoidome (eCBome), counteract food intake and obesity. In this exploratory study, we examined the blood and stools from a subset of the participants in a cohort of reproductive-aged women with overweight/obesity who underwent a 12-week caloric restriction of 500 kcal/day wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 93 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…Capsimax is a readily available capsaicin supplement containing 2% capsaicinoids [1.2–1.35% capsaicin, 0.6–0.8% dihydrocapsaicin, and 0.1–0.2% nordihydrocapsaicin]) from 15–25% Capsicum extract, 45–55% sucrose, and 30–35% cellulose gum coatings [ 148 ]. Capsimax prolongs release into the small intestine, which therefore overcomes pungency and related issues associated with direct chilli or capsaicin application [ 148 , 149 , 150 , 151 ]. OmniActive Health Technologies dissolution studies indicate a range of 60–75% of the total capsaicinoids content of Capsimax are released within four hours and are completely released beyond six hours post-ingestion [ 149 ].…”
Section: Capsimaxmentioning
confidence: 99%
See 2 more Smart Citations
“…Capsimax is a readily available capsaicin supplement containing 2% capsaicinoids [1.2–1.35% capsaicin, 0.6–0.8% dihydrocapsaicin, and 0.1–0.2% nordihydrocapsaicin]) from 15–25% Capsicum extract, 45–55% sucrose, and 30–35% cellulose gum coatings [ 148 ]. Capsimax prolongs release into the small intestine, which therefore overcomes pungency and related issues associated with direct chilli or capsaicin application [ 148 , 149 , 150 , 151 ]. OmniActive Health Technologies dissolution studies indicate a range of 60–75% of the total capsaicinoids content of Capsimax are released within four hours and are completely released beyond six hours post-ingestion [ 149 ].…”
Section: Capsimaxmentioning
confidence: 99%
“…A decrease in calorie consumption of 257 kcal per day and increased serum high-density lipoprotein (HDL) was reported in participants given 200 mg Capsimax, compared to 100 mg Capsimax or placebo at 12 weeks. Similarly, a 12-week study comparing 200 mg Capsimax or placebo alongside a calorie-restricted diet reported reductions in body weight, BMI, waist circumference, and fat mass in overweight and obese women of reproductive age [ 150 ]. This study reported a high dropout rate of 27%, which was due to the difficulties of compliance with the prescribed restrictive diet rather than side effects of the intervention.…”
Section: Capsimaxmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Nutrition 06 frontiersin.org 12 weeks while taking either capsaicin or a placebo (45). To evaluate the effects of the intervention, pre-and post-intervention blood and stool samples were subjected to LC-MS/MS, wherein the plasma levels of eCBome mediators and 16S metagenomic sequences in fecal microbiome taxa were analyzed.…”
Section: Micementioning
confidence: 99%
“…A further study showed that the oral use of the capsaicinoids (the pungent principles of chilli peppers and prototypical activators of the transient receptor potential of the vanilloid type-1 channel administration) alters the plasma endocannabinoidome and faecal microbiota of reproductive-aged women living with overweight and obesity [3].…”
mentioning
confidence: 99%